Comparing two mathematical competencies frameworks from China and Denmark. Issue 4 (December 2022) - Hong, Yanjun; Jankvist, Uffe Thomas
In this article, we compare two disciplinary competency descriptions of mathematics. More precisely, we describe and compare the Core Mathematics Competencies (CMC) framework in the Chinese mainland with the Danish mathematics competencies framework (KOM). We look for similarities and differences in the conceptualization of "competency", the structure of the two frameworks as well in their specific competency descriptions and ask the question of how to articulate any identified similarities and differences. Relying on a distinction between disciplinary competency descriptions for internal and for external use, we conclude that while KOM is to be regarded as a more or less classical competency description for internal use, that is, one that facilitates communication between various practitioners within a discipline, CMC encompasses more aspects of a competency description for external use, that is, it also facilitates communication between practitioners and recipients.